PENERAPAN MODEL TRI PRAMANA SPA DITINJAU DARI MOTIVASI SISWA TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Arjaya, Ida Bagus Ari; Puspadewi, Kadek Rahayu (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2017)
The purposes of this research are to analyze: 1) The difference of critical thinking ability between Model Tri Pramana SPA (MTPSPA) and Model Pembelajaran Konvensional (MPK), 2) the differences in critical thinking skills between MTPSPA and MPK in students with high learning motivation, 3) The differences in critical thinking skills between MTPSPA and MTPSPA in students with low learning motivation, 4) The interactive effect between learning model and learning motivation toward students' critical thinking ability. The population of this study was all students of SMP Negeri 7 Denpasar academic year 2016/2017. The Samping technique that was used was group random sampling method with a quasi experiment design. The prerequisite data analysis consisted of internal validity analysis and interrater reliability. Two Way Analyze of Variant (ANAVA) by using SPSS 17 for Windows Software was used as the data analysis technique. The result of the present study are 1) there was significant difference of students’ critical thinking between MTPSPA and MPK (p=0,000 < α = 0,05), 2) there was significant difference of students’ critical thinking between MTPSPA and MPK for high motivation (p=0,000 < α = 0,05), 3) there was significant difference of students’ critical thinking between MTPSPA and MPK for low motivation (p=0,000 < α = 0,05), 4) there is no interaction effect between learning model and students’ learning motivation toward students' critical thinking (p = 0,482> α = 0,05).